Corrosion Rates of Steel in Concrete 1990
DOI: 10.1520/stp25013s
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Effort to Use the Corrosion Rate Measurements for Estimating Rebar Durability

Abstract: The approach presented here is an attempt to implement the values of corrosion intensity which have been measured in laboratory tests, in the framework of the service life prediction analysis for corroding structures. First of all, the model on service life suggested by Tuuti was considered, and only the propagation period model has been analyzed in this paper. In order to expand the proposal, different steps were covered: (1) the definition of an unacceptable level of deterioration, taking into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 3 publications
3
57
0
4
Order By: Relevance
“…This investigation agrees weB with the results of the study by Andrade et al (1990), who suggested that a reduction of lOto 25 percent in the bar section in the critical zones of the structure will result in the depletion of its service life, while a reduction up to 5 percent, even with cracking and spalling, will indicate an early stage of deterioration with the remaining service life not as significantly influenced, provided that adequate repairs are undertaken urgently.…”
Section: Relative Bond Performance Ofcorroded Barssupporting
confidence: 91%
See 1 more Smart Citation
“…This investigation agrees weB with the results of the study by Andrade et al (1990), who suggested that a reduction of lOto 25 percent in the bar section in the critical zones of the structure will result in the depletion of its service life, while a reduction up to 5 percent, even with cracking and spalling, will indicate an early stage of deterioration with the remaining service life not as significantly influenced, provided that adequate repairs are undertaken urgently.…”
Section: Relative Bond Performance Ofcorroded Barssupporting
confidence: 91%
“…Mass losses up to 5 percent can cause the element to crack and spall, however, this is an early stage of deterioration with the remaining service life not as significantly influenced, provided that adequate repairs are undertaken urgently. However, a 10-25 percent mass loss in the critical zones of the structure will result in the depletion of its service life (Andrade et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…CR were calculated using the expression CR=k.B/R p where B is a constant that depends on the active/passive state of the steel: B is equal to 0.026 V, in the case the steel is in the active state, and 0.052 V in the case of passive state [10]. k is a constant that relates corrosion current densities and CR by applying Faraday´s Law [k= 11.6 (µm/year)/(µA/cm 2 )].…”
Section: Resultsmentioning
confidence: 99%
“…For corrosion propagation, Andrade et al [21] employed the Tuutti conceptual model to estimate the loss in reinforcing bar cross section during the propagation period as:…”
Section: Modeling Of Corrosion Based On Acoustic Emission Datamentioning
confidence: 99%